Seasonal monitoring of blue mussel (Mytilus spp.) populations in a harbor area: A focus on responses to environmental factors and chronic contamination. (August 2017) - Lacroix, C.; Duvieilbourg, E.; Guillou, N.; Guyomarch, J.; Bassoulet, C.; Moraga, D.; Chapalain, G.; Auffret, M.
Abstract: Coastal waters corresponding to macrotidal systems are among the most variable marine biotopes. Sessile animals as bivalve mollusks may however be found forming intertidal beds at high densities, as allowed by full adaptation to local conditions. A better knowledge of adaptive responses to environmental factors is required to foresee possible adverse effects of global change. At the sub-cellular level, transcriptional responses are among the earliest signals of environmental disturbances and they can reveal subtle and meaningful changes in organism exposed to stress. Three blue mussel ( Mytilus spp. ) populations inhabiting the Bay of Brest (France) in sites exposed to different levels of chronic pollution, from low to moderate, were surveyed upon a seasonal schedule, with special attention to the reproductive cycle. Major seawater parameters were monitored over a full-year in the framework of the S!RANO project, based on an automatic high frequency acquisition system installed aboard a ship of opportunity. The health status of mussels has been assessed by measuring a condition index and gametogenesis has been followed by histology. Selected biological responses to environmental stress were detected using a multimarker approach including expression of genes involved in chemical stress response and energetic metabolism, and cellular immune parameters. Environmental parameters showed deep seasonal variations which differed among sites. Most biological responses followed a seasonal pattern. Late winter and spring corresponded to an active reproduction period in the Bay of Brest. Earlier spawning was observed in harbor areas compared to the oceanic site and an altered physiological state was assumed in commercial harbor mussels during the reproductive period, suggesting that their health is compromised at this time of year. However, no signs of severe chemical stress were detected in both harbor mussel populations, which could reflect adaptive responses to adverse environmental conditions. Highlights: A ship of opportunity provided measurements of natural environmental conditions in sampling sites. Blue mussel health was investigated in moderately chronically polluted areas at different seasons. Immune responses and gene expressions followed seasonal patterns. Health was compromised during the active reproduction period at a harbor site. Mussels expressed adaptive responses to chronic exposure to moderate contamination levels.